Hubungan Komunikasi Corporate Social Responsibility dengan Reputasi Perusahaan - Damayanti Syahriani; Mahmudi Siwi (Institut Pertanian Bogor, 2018)
The Corporate Social Responsibility (CSR) program is a form of corporate social responsibility in reducing the impact of the company's business activities. CSR programs should be supported by communication strategies so that their implementation will be effective. In each company has a different CSR communication strategy. The implementation of this CSR communication strategy has an impact on the company's reputation, it is a very important part to support the sustainability of a company. The purpose of this paper is to identify corporate communication strategies in implementing CSR programs and the relationship of CSR communication strategies to the company's reputation. This research was conducted in Malasari Village, Nanggung District, Bogor Regency, West Java using a quantitative approach supported by qualitative data. The quantitative approach is carried out by clustering in the three existing programs with a total of 40 respondents. The results of this study indicate that there is a relationship between the characteristics of the sender of messages with the effectiveness of CSR messages, communication strategies with the effectiveness of CSR messages and the effectiveness of CSR messages with company reputation.